Social media and election under covid-19 pandemic in Malang regency Indonesia - Nurjaman, Asep; Hertanto, Hertanto (International Journal of Communication and Society, 2022)
Since COVID-19 is a global epidemic that threatens the safety of mankind, reducing the risk of transmitting the virus is an important issue in the implementation of elections in Indonesia. The purpose of this study is to describe the impact of the use of social and mass media on the implementation of elections. This research was conducted in Malang Regency using a qualitative descriptive approach. Data collection was carried out through limited interviews, observation, and document analysis gathered from books, journals, and election documents. The results of the study show that (1) election information and campaigns are mostly done through social and mass media; (2) most of the public can receive information and campaign issues conveyed through the mass media; (3) elections can run well and smoothly. These findings indicate that the use of social and mass media for socialization and campaigning during a pandemic is quite effective. This finding is very important to reduce the spread of COVID-19, as well as to encourage the implementation of a more modern election.